New environmental NGOs in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Two regional NGOs dealinc with environmental issues have recently been established in Africa. TRENCOP (Tree and Energy Conservation Project) is based in Uganda where it works on tree plantations and improved woodstoves. In Rwanda, a research and...